Tideglusib, a prospective alternative to nonoxynol-9 contraceptive - Zhiting Chen; Niyan Shu; Yuzhu Wang; Yiting Yang; Zhiyu Shao; Fang Tian; Minjie Xia; Zhikai Wang; Xin Wang; Xing Feng; Xianliang Huang; Weihua Li; et al. (Elsevier, 2019)
Objectives: We aimed to evaluate the antifertility activity and vaginal irritation effects of tideglusib in vivo using rabbit models and to evaluate the cytotoxical effects of tideglusib to sperm, vaginal cells and vaginal bacteria (L. acidophilus) in vitro. Study design: We treated female rabbits with vaginal tideglusib 1 mM, nonoxynol-9 (N-9) or vehicle control (Poloxamer 407). In experiment 1, we sacrificed females (n = 6 each) after 10 days of daily administration and assessed vaginal histological changes using Eckstein irritation score. In experiment 2, females (n = 9 each) received estradiol benzoate to induce ovulation 24 h prior to vaginal treatment followed by introduction of a fertile male. These females underwent necropsy at the 21st day to assess pregnancy status. In experiment 3, we used an HTM-TOX IVOS sperm motility analyzer and scanning electron microscopy (SEM) to evaluate the effect of tideglusib on human sperm samples. In experiment 4, we evaluated the effect of tideglusib on lactobacillus and vaginal cell growth in vitro. Results: The total irritation score of tideglusib vs. N-9 was 3.4 ± 2.07 vs. 7.8 ± 3.82, p<.05. The pregnancy rate of tideglusib, N-9 and control group was 11.1%, 0% and 88.9%, respectively. Tideglusib exhibited a dose-dependent spermostatic/spermicidal activity, and the minimum effective concentrations of tideglusib and N-9 were 8.724 ± 3.047 μM and 219.75 ± 41.78 μM, respectively. SEM and transmission electron microscopy revealed acrosomal membrane impairments caused by tideglusib. Tideglusib was much less toxic to vaginal cells and L. acidophilus than N-9 in vitro. Conclusions: Evaluation using rabbit models indicated that tideglusib is a prospective spermicidal contraceptive with low vaginal irritation effects. Implications: Tideglusib or tideglusib analogues may be a contraceptive with perspective to replace N-9. It is possible for a spermicide to balance spermicidal activity and vaginal/cervical irritation effects very well. Keywords: Tideglusib, Sperm, Contraceptive, Nonoxynol-9, Spermicide